Pengaruh Akumulasi Tenaga Non Aerobik terhadap Beberapa Variabel Fungsional dan Laktat Darah pada Pelari Jarak Menengah - Gorgees, Shatha Hazim (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to investigate the effects of non-aerobic (anaerobic) effort accumulation on select functional variables and blood lactate concentrations in middle-distance runners. A diverse cohort of experienced middle-distance runners was recruited for this study. Materials and methods. The study involved 30 experienced middle-distance runners. The participants engaged in a series of controlled, high-intensity anaerobic exercises to induce the accumulation of anaerobic effort. Following these exercises, we measured a range of functional variables, including maximal oxygen uptake (VO2 max), heart rate, stroke volume, critical indicators of cardiovascular function, and aerobic fitness. Simultaneously, blood samples were drawn from the participants before and after the exercise regimen to quantify blood lactate levels. Results. The VO2 max showed a slight decline post-exercise (58.7 ± 6.4 mL/kg/min) compared to the baseline measure (61.3 ± 6.7 mL/kg/min). In addition, there was a significant increase in heart rate post-exercise (185.4 ± 8.6 beats/min) compared to pre-exercise (79.2 ± 8.3 beats/min). Conclusions. The decrease in VO2 max post-exercise indicated a decline in aerobic performance, a typical response to high-intensity exercise. Also, the rise in lactate concentrations post-exercise and the subsequent decrease during recovery provided evidence of anaerobic metabolism during high-intensity exercise and the body's efficient lactate clearance mechanism during recovery. This study contributes to understanding lactate metabolism during and after high-intensity exercise. The findings also contribute to understanding how the body adapts to exercise and have potential implications for designing training and recovery strategies for athletes.